Sudden Development of Fatal Pulmonary due to Suspected Pulmonary Tumoral Thrombotic Microangiopathy among Patients with Cancer: Case Series of Clinical and CT Features in 10 Patients - Bo Kyung Kim; Yookyung Kim; Kyung Eun Lee (Journal of the Korean Society of Radiology)
Pulmonary tumoral thrombotic microangiopathy (PTTM) is a rare but fatal complication in patients with cancer that causes death due to sudden respiratory distress, pulmonary hypertension, and right ventricular dysfunction. Early diagnosis and intensive treatment are important for improving patient prognosis. Herein, we describe the clinical and CT findings of 10 patients who were clinically diagnosed with PTTM at our hospital over the past 18 years. In patients with cancer complaining of dyspnea and hypoxia, CT findings such as right ventricular and pulmonary artery dilatation, perivascular or subpleural ground-glass opacity or consolidation, micronodules with a ground-glass halo, peripheral pulmonary vessel dilatation, and interlobular septal thickening may suggest PTTM.